Fundamental edge broadening effects during focused electron beam induced nanosynthesis - Schmied, Roland; Fowlkes, Jason D.; Winkler, Robert; Rack, Phillip D.; Plank, Harald (Beilstein Journal of Nanotechnology, 2015)
The present study explores lateral broadening effects of 3D structures fabricated through focused electron beam induced deposition using MeCpPt(IV)Me3 precursor. In particular, the scaling behavior of proximity effects as a function of the primary electron energy and the deposit height is investigated through experiments and validated through simulations. Correlated Kelvin force microscopy and conductive atomic force microscopy measurements identified conductive and non-conductive proximity regions. It was determined that the highest primary electron energies enable the highest edge sharpness while lower energies contain a complex convolution of broadening effects. Moreover, it is demonstrated that intermediate energies lead to even more complex proximity effects that significantly reduce lateral edge sharpness and thus should be avoided if desiring high lateral resolution.
Keywords: focused electron beam induced deposition; nanofabrication; platinum; simulation

(untitled) - Randolph, S. J.; Fowlkes, J. D.; Rack, P. D. (Crit. Rev. Solid State Mater. Sci., 2006)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

Nanofabrication using focused ion and electron beams: principles and applications - Utke, I.; Russell, P. E. (Oxford University Press, 2012)

(untitled) - Van Dorp, W. F.; Hansen, T. W.; Wagner, J. B.; De Hosson, J. T. M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Bret, T.; Utke, I.; Bachmann, A.; Hoffmann, P. (Appl. Phys. Lett., 2003)

(untitled) - Utke, I.; Gölzhäuser, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Plank, H.; Gspan, C.; Dienstleder, M.; Kothleitner, G.; Hofer, F. (Nanotechnology, 2008)

(untitled) - Plank, H.; Haber, T.; Gspan, C.; Kothleitner, G.; Hofer, F. (Nanotechnology, 2013)

(untitled) - Utke, I.; Friedli, V.; Purrucker, M.; Michler, J. (J. Vac. Sci. Technol., B, 2007)

(untitled) - Fowlkes, J. D.; Rack, P. D. (ACS Nano, 2010)

(untitled) - Smith, D. A.; Fowlkes, J. D.; Rack, P. D. (Small, 2008)

(untitled) - Fowlkes, J. D.; Randolph, S. J.; Rack, P. D. (J. Vac. Sci. Technol., B, 2005)

(untitled) - Van Oven, J. C.; Berwald, F.; Berggren, K. K.; Kruit, P.; Hagen, C. W. (J. Vac. Sci. Technol., B, 2011)

(untitled) - Van Dorp, W. F.; Wnuk, J. D.; Gorham, J. M.; Fairbrother, D. H.; Madey, T. E.; Hagen, C. W. (J. Appl. Phys., 2009)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Fairbrother, D. H. (J. Phys. Chem. C, 2009)

(untitled) - Plank, H.; Smith, D. A.; Haber, T.; Rack, P. D.; Hofer, F. (ACS Nano, 2012)

(untitled) - Smith, D. A.; Fowlkes, J. D.; Rack, P. D. (Nanotechnology, 2008)

(untitled) - Mulders, J. J. L.; Belova, L. M.; Riazanova, A. (Nanotechnology, 2011)

(untitled) - Córdoba, R.; Sesé, J.; De Teresa, J. M.; Ibarra, M. R. (Microelectron. Eng., 2010)

(untitled) - Roberts, N. A.; Fowlkes, J. D.; Magel, G. A.; Rack, P. D. (Nanoscale, 2013)

(untitled) - Roberts, N. A.; Magel, G. A.; Hartfield, C. D.; Moore, T. M.; Fowlkes, J. D.; Rack, P. D. (J. Vac. Sci. Technol., A, 2012)

(untitled) - Langford, R. M.; Ozkaya, D.; Sheridan, J.; Chater, R. (Microsc. Microanal., 2004)

(untitled) - Gopal, V.; Stach, E. A.; Radmilovic, V. R.; Mowat, I. A. (Appl. Phys. Lett., 2004)

(untitled) - Botman, A.; Mulders, J. J. L.; Weemaes, R.; Mentink, S. (Nanotechnology, 2006)

(untitled) - Langford, R. M.; Wang, T.-X.; Ozkaya, D. (Microelectron. Eng., 2007)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Schwalb, C. H.; Grimm, C.; Baranowski, M.; Sachser, R.; Porrati, F.; Reith, H.; Das, P.; Müller, J.; Völklein, F.; Kaya, A.; Huth, M. (Sensors, 2010)

(untitled) - Frabboni, S.; Gazzadi, G. C.; Felisari, L.; Spessot, A. (Appl. Phys. Lett., 2006)

(untitled) - Plank, H.; Kothleitner, G.; Hofer, F.; Michelitsch, S. G.; Gspan, C.; Hohenau, A.; Krenn, J. (J. Vac. Sci. Technol., B, 2011)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Sachser, R.; Reith, H.; Huzel, D.; Winhold, M.; Huth, M. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Perentes, A.; Bachmann, A.; Leutenegger, M.; Utke, I.; Sandu, C.; Hoffmann, P. (Microelectron. Eng., 2004)

(untitled) - Utke, I.; Jenke, M. G.; Röling, C.; Thiesen, P. H.; Iakovlev, V.; Sirbu, A.; Mereuta, A.; Caliman, A.; Kapon, E. (Nanoscale, 2011)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belić, D.; Bertagnolli, E. (ACS Nano, 2013)

(untitled) - Gabureac, M. S.; Bernau, L.; Boero, G.; Utke, I. (IEEE Trans. Nanotechnol., 2013)

(untitled) - Serrano-Ramón, L.; Córdoba, R.; Rodríguez, L. A.; Magén, C.; Snoeck, E.; Gatel, C.; Serrano, I.; Ibarra, M. R.; De Teresa, J. M. (ACS Nano, 2011)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Gabureac, M.; Bernau, L.; Utke, I.; Boero, G. (Nanotechnology, 2010)

(untitled) - Porrati, F.; Sachser, R.; Schwalb, C. H.; Frangakis, A. S.; Huth, M. (J. Appl. Phys., 2011)

(untitled) - Kolb, F.; Schmoltner, K.; Huth, M.; Hohenau, A.; Krenn, J.; Klug, A.; List, E. J. W.; Plank, H. (Nanotechnology, 2013)

(untitled) - Hari, S.; Hagen, C. W.; Verduin, T.; Kruit, P. (J. Micro/Nanolithogr., MEMS, MOEMS, 2014)

(untitled) - Arnold, G.; Timilsina, R.; Fowlkes, J.; Orthacker, A.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Winkler, R.; Fowlkes, J.; Szkudlarek, A.; Utke, I.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2014)

Code::Blocks

(untitled) - Winkler, R.; Geier, B.; Plank, H. (Appl. Phys. A, 2014)

(untitled) - Drouin, D.; Couture, A. R.; Joly, D.; Tastet, X.; Aimez, V.; Gauvin, R. (Scanning, 2007)

(untitled) - Botman, A.; de Winter, D. A. M.; Mulders, J. J. L. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Van Dorp, W. F. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Spencer, J. A.; Rosenberg, S. G.; Barclay, M.; Wu, Y.-C.; McElwee-White, L.; Howard Fairbrother, D. (Appl. Phys. A, 2014)

(untitled) - Winkler, R.; Szkudlarek, A.; Fowlkes, J. D.; Rack, P. D.; Utke, I.; Plank, H. (ACS Appl. Mater. Interfaces, 2015)

Microelectronic Engineering - Bret, T.; Utke, I.; Hoffmann, P.; Abourida, M.; Doppelt, P. (Electron range effects in focused electron beam induced deposition of 3D nanostructures, Micro- and Nano-Engineering MNE 2005, Vienna, Austria, 19.9.2005-22.9.2005, 2006)